Identification and risk assessment of coal mining-induced landslides in Guizhou Province by InSAR and optical remote sensing - ZHU Yifei; YAO Xin; YAO Leihua; ZHOU Zhenkai; YAO Chuangchuang; XIAO Shihao (Dizhi lixue xuebao, 2022)
The Zongling landslide group in Guizhou Province is characterized by strong regularity of disaster formation, concentrated development and severe threat. It is represented in the coal mining-induced geological hazards in western Guizhou and eastern Yunnan. In this paper, InSAR and optical remote sensing were used for nuanced identification to obtain the regional landslide information, and the landslide deformation-failure mode in the Zongling region was summarized. Based on this, the volume-distance statistical formula suitable for landslide risk assessment in this region was established, and the typical disaster bodies ware calculated. Some important insights are gained: Underground coal mining is the major contributor to the deformation of the edge of Table Mountain in Zongling. InSAR observation results show that the deformation in the Zongling area has prominent zonal characteristics, and the annual average deformation velocity is between -20.4~10.2 cm/a, which corresponds well with the lower goaf. The areas with great displacement are concentrated in the edge zone of cuesta, with coal mining subsidence and slope gravity superimposed; There are 64 deformations in the Zongling area, including 37 landslides, 27 cracks, and 2 dangerous deformed bodies. Landslides mainly occur in the dark grey limestone strata and dark purplish-red argillaceous siltstone strata of the Feixianguan Formation. According to the lithology and deformation characteristics of the slip source, the landslides can be classified into two types: pull-toppling and pull-clipping, and the former is distinguished by large particle size, long movement distance, and severe threat. The formula for calculating the slip distance of rock landslide debris flow has good applicability to the slip distance of coal mining-induced landslide developed in the "upper hard and lower soft" strata in the Zongling area, and the verification error is less than 5%. The formula is used to calculate the dangerous deformed bodies of Zuojiaying and Jingjiao in the study area, and the danger avoidance distance is predicted to be 220~386 m. The proposed method of coal mining-induced landslide risk assessment based on differential interferometry and optical image play an exemplary role for the prevention and control of coal mining-induced landslides in western Guizhou and eastern Yunnan.